Coordinated Analysis of Primordial Components within Primitive Astromaterials: Implications for the Presolar Environment and the Formation of the Protoplanetary Disk - Nevill, Nicole Dawn (Curtin University, 2022)
The smallest and oldest astromaterials recorded processes leading to presolar and Solar System formation. This thesis documents the first successful petrographic analyses of these astromaterials using unique methodologies and high-resolution techniques down to the atomic level. Results demonstrated the power and importance of modifying established approaches to examine these analytically challenging materials. This work provided new insights into abiotic organic evolution; water/rock relationships; physical and chemical processing within presolar, interstellar medium and solar nebula environments.